VALIDASI DAN PENGEMBANGAN PARADIGMA EKSPERIMEN LEARNED HELPLESSNESS PADA ETNIS DOMINAN DI INDONESIA - Galang Lufityanto (PSIKODIMENSIA, 2018)
Learned helplessness (LH) is known as a phenomenon in which participants feel powerless toward the conditions occurred to them. While the phenomenon can be attributed to other psychological phenomena such as depression, etc. little is known whether specific context would explain (i) what the cause of (LH) and (ii) what strategy employed by individuals to cope with LH. Our study is intended to examine the two above questions in the dominant ethnicity in Indonesia, i.e. Javanese. Sixty participants were interviewed with open-ended questionnaire following indigenous psychology approach. We found that family was the greatest cause of LH in our sample. Further spiritual activities were employed by our participants to deal with their feeling of powerless.